THE INFLUENCE OF GROUP DYNAMICS TO STUDENTS' CREATIVITY IN BUSINESS MANAGEMENT CLASS OF UNIVERSITAS CIPUTRA - Dewi, Liliana (Universitas Brawijaya, Indonesia, 2019)
The education world has significant roles in encouraging students to be productive, collaborative, and communicative in this competitive era. Therefore, educators should be able to administer classes where students can experience learning process to have the necessary skills in working environment. One way to establish the desired learning process is by designing and setting special learning groups in the classroom as an environment to develop students'social skills and their productivity. The desired environment is an environment which nurtures students'creativity in developing their social skills and productivity, namely group dynamics. To achieve this goal, a qualitative research is conducted in marketing management classes in Ciputra University Surabaya, Indonesia, to see if setting a dynamics environment are able to grow students'creativity. In several similar cases, educators believe in the need of organizing learning groups which fit the development of twenty first century. Dynamics environment is needed to grow students' creativity. The research will contribute some knowledge on how higher education educators organize and set learning groups in big class. The results of the research will suggest some ways to organize and set the learning groups which are effective in developing students'creativity.